Curriculum for Digital Information Systems: A Learning Package for Library and Information Professionals - Gopinath, M. A. (Journal of Information and Knowledge, 1998)
Developments in information technology have continuously promoted need for newer strategies in the management of information. Information professionals have the cause to learn much about digital technology. After discussing constraints in curriculum for digital information systems a learning package is delineated for an advanced course for information professionals.